Numerical investigation on thermal performance of plate-fin heat sink designs subjected to parallel and impinging flow / Muhammad Zarif Shaharudin…[et al.] - Shaharudin, Muhammad Zarif; Mohd Shawal, Mohd Syahar; Mahat, Mohamad Mazwan; Saedon, Juri; Meon, Mohd Suhairil; Abdul Rahman, Mohd Rosdzimin (Smart Manufacturing Research Institute (SMRI), 2023)
The electronic industry has been working for decades to improve the cooling efficiency of heat sinks by creating more advanced, efficient cooling technologies. However, heat dissipation remains the major problem due to the designs complexity and limited space for cooling devices. This paper investigates the effect of flow direction on the thermal performance for the proposed designs. The removed material from the fin base to create the fillet was re-used to form half-round pin that was attached to the plate-fin, in symmetrical and corrugated arrangements. Plate-fin heat sinks with and without fillet profiles were investigated and two new proposed designs for plate-fin heat sinks with half-round pins attached to the fin were developed in this study. Numerical analysis was performed using ANSYS FLUENT R21 to evaluate the thermal performance of the proposed designs. For the element optimization, the grid independency test was performed to obtain the optimal number of elements. A constant heat flux of 18.75 kW/m2 was applied at the bottom plate of heat sinks as the input parameter and two different flow directions e.g., impinging flow and parallel flow at various mass flow rate was also applied to study the base temperature, thermal resistance and Nusselt number of these designs. The study has shown that plate-fin heat sinks with fillet profile and corrugated half-round pins (PFHS 4) subjected to parallel flow and plate-fin heat sinks with fillet profile and symmetrical half-round pins (PFHS 3) subject to impinging flow exhibit better thermal performance over other configurations. Hence, these plate-fin designs have the potential to be practically applied as heat sinks for electronic devices.